The Role of Higher Education in Implementing Pancasila Education MKWU Policy for National Character Development - Tatang Sudrajat (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
The character of the nation is very important for the sustainability of the Indonesian nation's struggle to fill independence by carrying out national development. Value education, including Pancasila Education in tertiary institutions plays a strategic role in preparing nationals with character. Public policy in the field of higher education is a concrete manifestation of the state's function in educating the nation's life. This study aims to describe the role of higher education institutions in implementing the MKWU Pancasila Education policy for the development of national character. With the normative juridical method and literature study, it is known that the state / government has established a policy of inculcating the values of Pancasila by issuing several public policies in the field of higher education. Universities as policy institutions as well as university leaders and lecturers of MKWU Pancasila Education as policy actors play a major role in building student character as an integral part of the Indonesian nation. Students as policy targets can act as role models for successful implementation. The policy environment contributes to its survival and success. Higher education is faced with several challenges and problems in implementing the policy of planting Pancasila values. There is a policy substance that needs to be refined.